Research on the Correlation Between The Application Status of Digital Health Tools in Glaucoma Chronic Disease Management and Patients' Self-Management Efficacy - Wei, Shutong (International Journal of Public Health and Medical Research, 2026)
Glaucoma is an irreversible disease that seriously threatens vision. Chronic disease management involves continuous treatment, regular follow-up, and lifestyle interventions, which place high demands on patient compliance and initiative. With the development of digital technology, digital technology represented by applications, wearable sensor technology and the Internet has been widely used in the behavior management and disease prevention of glaucoma patients, such as taking medicine, eye pressure control, education and doctor patient interaction. In summary, this article attempts to summarize the current research results on the application of digital health tools in the self-management of glaucoma patients at home and abroad, while elaborating on the concept and importance of patient self-management efficacy, in order to explore whether the application of digital health tools affects patients' self-management efficacy and promote glaucoma patients to better complete disease self-management work. However, the degree of correlation between the two variables varies due to various factors such as tool category, tool attributes, user characteristics, and medical service environment. Therefore, this article proposes improvement plans including personalized tool matching suggestions, tool design that focuses on user needs, creating a multi-party cooperation platform, and implementing continuous tracking feedback to enhance the effectiveness of mobile health management, ultimately improving the long-term management quality and quality of life of glaucoma patients.